Effect of polarization potential on tribocorrosion behavior of duplex stainless steel UNS S32205 in NaCl solution - Jomar José Knaip Ribeiro; Oriana Palma Calabokis; Yamid Enrique Nuñez de la Rosa; Silvio Francisco Brunatto; Paulo César Borges (Engineering Science and Technology, an International Journal)
This study explores the effects of anodic, cathodic, and open circuit (OCP) potentials on the tribocorrosion behaviour of the UNS S32205 duplex stainless steel, which is largely used in oil, gas, and cellulose industry. For this purpose, tribocorrosion assays using a contact sphere (Si3N4) against the specimen plane in reciprocating sliding movement in 0.5 M NaCl solution were carried out. For comparison purposes, cathodic polarization or tests without applied potential under distilled water (DW) were used to inhibit corrosion for tribocorrosion tests. Two main distinct behaviours were observed: i) high coefficients of friction and lower wear volumes at the cathodic polarization (CP) for conditions smaller or equal to –0.8 V (vs Ag/AgCl 3 M) as well as in DW; and ii) low coefficients of friction and higher wear volumes for anodic polarization (AP), OCP, and CP for –0.4 V. The tribocorrosion behaviour of both groups was directly related to the chemical characteristics inside the tracks analyzed using SEM-EDS and Raman spectroscopy. All analyzed tracks showed similar oxygen contents and chemical compositions within each group. Finally, this study allowed the determination of the great effect of the potential applied on the tribocorrosion behaviour and the identification of differences between the cathodic protection and distilled water assays as methods to inhibit corrosion.